DYRK1A regulates the recruitment of 53BP1 to the sites of DNA damage in part through interaction with RNF169. Issue 5 (4th March 2019) - R. Menon, Vijay; Ananthapadmanabhan, Varsha; Swanson, Selene; Saini, Siddharth; Sesay, Fatmata; Yakovlev, Vasily; Florens, Laurence; DeCaprio, James A.; P. Washburn, Michael; Dozmorov, Mikhail; Litovchick, Larisa
ABSTRACT: Human Dual-specificity tyrosine (Y) Regulated Kinase 1A (DYRK1A) is encoded by a dosage dependent gene whereby either trisomy or haploinsufficiency result in developmental abnormalities. However, the function and regulation of this important protein kinase are not fully understood. Here, we report proteomic analysis of DYRK1A in human cells that revealed a novel role of DYRK1A in DNA double-strand breaks (DSBs) repair, mediated in part by its interaction with the ubiquitin-binding protein RNF169 that accumulates at the DSB sites and promotes homologous recombination repair (HRR) by displacing 53BP1, a key mediator of non-homologous end joining (NHEJ). We found that overexpression of active, but not the kinase inactive DYRK1A in U-2 OS cells inhibits accumulation of 53BP1 at the DSB sites in the RNF169-dependent manner. DYRK1A phosphorylates RNF169 at two sites that influence its ability to displace 53BP1 from the DSBs. Although DYRK1A is not required for the recruitment of RNF169 to the DSB sites and 53BP1 displacement, inhibition of DYRK1A or mutation of the DYRK1A phosphorylation sites in RNF169 decreases its ability to block accumulation of 53BP1 at the DSB sites. Interestingly, CRISPR-Cas9 knockout of DYRK1A in human and mouse cells also diminished the 53BP1 DSB recruitment in a manner that did not require RNF169, suggesting that dosage of DYRK1A can influence the DNA repair processes through both RNF169-dependent and independent mechanisms. Human U-2 OS cells devoid of DYRK1A display an increased HRR efficiency and resistance to DNA damage, therefore our findings implicate DYRK1A in the DNA repair processes.